EAPH-08. A PHASE I TRIAL OF TTFIELDS WITH AND WITHOUT CONCOMITANT TEMOZOLOMIDE AND BEVACIZUMAB IN PEDIATRIC PATIENTS WITH HIGH-GRADE GLIOMA. Issue 2 (22nd June 2018) - Hanson, Derek
Abstract: High-grade gliomas (HGG) comprise 8–12% of brain tumors in children and include anaplastic astrocytoma or glioblastoma multiforme (GBM) pathology. Treatment involves surgical resection, adjuvant radiation and chemotherapy. The prognosis of these tumors is poor and new therapies must be investigated to improve clinical outcomes for this patient population. Tumor Treating Fields (TTFs) is a non-invasive antimitotic treatment comprised of low-intensity alternating electric currents delivered through the Optune device approved for adults with GBM. This phase 1 study [NCT03128047] will include 2 cohorts of pediatric patients (N= 6–12), age ≥1 and <18 years, with histologically-confirmed supratentorial newly-diagnosed or recurrent HGG. This study will have two safety endpoints to assess the safety and tolerability of TTFields for the treatment of pediatric HGG both alone and in combination with temozolomide (TMZ) and bevacizumab (BEV). Cohort 1 will receive TTFields (200kHz 18 hours/day). Cohort 2 will receive TTFs plus BEV 10mg/kg/dose and TMZ 200 mg/m2/day. Safety endpoints will be determined by a standard 3 + 3 phase I study design based on the incidence and severity of adverse events and toxicities (CTC V4). There are no primary efficacy endpoints for this study. Patients will be followed to assess their progression-free and overall survival as the efficacy data gained from this study may be useful in designing future phase II/III investigations. The sample size will be determined by the number of observed severe adverse events related to therapy. A minimum of two and a maximum of twelve patients will be needed to complete this study.